1995
DOI: 10.1093/nar/23.3.515
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical analysis of DNA intrastrand cross linking by formation of 8,5′-cyclodeoxyadenosine

Abstract: Formation of intramolecular cross links by addition of C(5') deoxyribose radicals to the C(8)-N(7) double bond of an attached adenine base was analyzed by ab initio quantum-chemical methods. Conformational preferences that influence the stereospecificity of the reaction were investigated. A good correlation was found between the ratio of experimental yields of R and S stereoisomers of 8,5'-cyclodeoxyadenosine and the relative energy of conformations of the C(5) radical that are precursors to these isomers. Mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 25 publications
4
37
0
Order By: Relevance
“…Thermodynamic studies have shown the highest stability for compound 3 [10]. For this reason the alkoxy radical (O5') of dA can become a precursor of compounds 12 and 13.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thermodynamic studies have shown the highest stability for compound 3 [10]. For this reason the alkoxy radical (O5') of dA can become a precursor of compounds 12 and 13.…”
Section: Resultsmentioning
confidence: 99%
“…However, the appearance of 12 and 13 will terminate the DNA elongation process, and from this point of view will be highly toxic for cells. Comparison of selected geometry properties of 3 calculated by B3LYP/DZP++ [10] and B3LYP/6-31G** in gas phase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their frequency and level in a living cell is still an open question, even though some data covering this field exists in literature [8]. Cyclopurines disturb the spatial geometry of DNA, weakening the hydrogen bonds between complementary bases in the double helix [9,10]. Moreover, they are more exposed to the influence of free radicals, therefore, their level in DNA can be upset due to forward reactions.…”
Section: Introductionmentioning
confidence: 99%